芬蘭教師的數學探究教學模式設計：以「縮圖與比例尺」為例 Mathematical Inquiry Teaching Model Design for a Primary School Teacher in Finland: Using "Thumbnail Figure and Scale" As an Example - 陳玟樺 Wen-Hua Chen Abstract (Higher Education Foundation, 2020)
數學探究教學在數學課堂一向具有重要性。本研究以一位芬蘭公立中小學教師為例，觀察和訪談其所發展的數學探究教學模式設計理念和其內涵。研究發現： 一、數學探究教學模式設計理念主要在促進自主學習和深度理解；二、數學探究教 學模式和其內涵涉有跨領域學習成分與「學習如何學習」探索，數學探究教學意涵 較以往有所擴充。本研究最後針對數學探究教學模式提出建議，以供臺灣本土數學教育工作者參考。 Mathematical inquiry teaching has always been important in the mathematics classroom. This study uses a Finnish primary school teacher to observe and interview his philosophy and model design for the teaching of mathematical inquiry. Two key findings emerged from this study. First, the case teacher's philosophy of the mathematical inquiry teaching design is to promote self-directed learning and deeper understanding. Second, the mathematical inquiry teaching model involves cross-domain learning and an exploration of "learning how to learn," broadening the meaning of mathematical inquiry teaching. This study also provides several suggestions for Taiwan educators on the design of mathematical inquiry teaching.